From Education to Action—The Impact of Hepatitis C Micro‐Elimination Education on Healthcare Provider Confidence and Linkage to Care: A Quasi‐Experimental Study - Regan Preston; Eric Lim; Shirley McGough; Glenn Boardman; Karen Heslop (Health Science Reports)
ABSTRACT Background and Aim Micro‐elimination education can improve access to life‐saving treatments for patients with hepatitis C, co‐occurring mental health conditions, and alcohol and other drug use disorders. The Hepatitis C virus (HCV) is disproportionately prevalent among people with mental health conditions and alcohol and other drug issues, reducing their life expectancy. Although hepatitis C is a curable condition, this population frequently remains untested and untreated. Micro‐elimination programs are necessary to enhance hepatitis C virus screening and treatment rates. This study aims to evaluate the impact of micro‐elimination education on healthcare providers' confidence in identifying high‐risk HCV populations, conducting HCV screenings and treatments, and managing comorbid substance use disorders. Additionally, it will assess referrals to a nurse‐led HCV treatment clinic. Methods A quasi‐experimental pre‐posttest intervention design was used. The intervention was an education program targeted at HCV micro‐elimination and linkage to care. Results Questionnaires were administered to (n = 101) healthcare providers to measure changes in confidence in screening and treating HCV in people with comorbid mental health conditions and alcohol and other drug disorders pre‐ and post‐intervention. Pre‐intervention, healthcare providers reported the highest confidence levels in treating mental health conditions. A significant increase in post‐education confidence in screening and treating the HCV across all healthcare provider roles was observed (p < 0.05). Twenty‐three referrals were received at the nurse‐led hepatitis C virus treatment clinic, with the majority (n = 11) of referrals received from nurses. Conclusion This study underscores the significance of micro‐elimination education programs in enhancing healthcare provider confidence in treating hepatitis C. Leveraging the mental health nursing workforce to connect high‐risk populations with hepatitis C care will expand timely access to life‐saving treatments and optimize healthcare outcomes. Targeted hepatitis C micro‐elimination education will further accelerate progress toward the 2030 elimination goals, enhancing the overall well‐being of vulnerable populations.